Initial experience with locoregional radioimmunotherapy using 131I-labelled monoclonal antibodies against tenascin (BC-4) for treatment of glioma (WHO III and IV) - Pöpperl, G.; Götz, C.; Gildehaus, F.-J.; Yousry, T. A.; Reulen, H. J.; Hahn, K.; Tatsch, K. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: None of the established treatments (surgery, radiotherapy, chemotherapy) for malignant glioma has improved its very poor prognosis. Adjuvant locoregional radioimmunotherapy (RIT) represents a new therapeutic approach. We present our initial experience with this therapeutic tool with respect to adverse effects, biokinetics and clinical follow-up. Methods: Following surgery and radiotherapy, 12 patients with glioma (4, WHO stage III; 8, WHO stage IV) underwent 1-5 RIT-cycles (average dose 1100 MBq 131labelled monoclonal BC-4 antibodies) at six week intervals. Follow-up included serial FDG-PET and MRI investigations. Evaluation of biokinetics included whole body scans, together with analysis of blood, urine and fluid from the tumor cavity. Results: Following RIT, four patients experienced temporary seizures, which, in one case, were associated with temporary aphasia. Eight patients developed HAMA (human anti-mouse antibodies) during follow-up. Mean biologic half-life of the radiopharmaceutical in the resection cavity was 3.9 d (range: 1.0-10.2 d) and remained stable intraindividually during further RIT-cycles. The antibody/radionuclide conjugate remained stable in the tumor cavity for at least 5 d. Median survival presently stands at 18.5 months compared to 9.7 months in a historical patient group (n = 89) undergoing conventional therapeutic strategies. Five patients show no signs of recurrence. In three patients with post-surgical evidence of residual tumor, one patient showed partial remission, one stable disease, and one progressive disease during RIT. Four patients without evidence of residual tumor mass at the beginning of RIT developed recurrence during therapy. Conclusions: Initial experience demonstrates that locoregional RIT is a well tolerated treatment modality that may represent a promising new approach in the management of patients with malignant glioma. Advantages of local application include passage of the blood-brain barrier, high concentration of activity within the resection cavity and low systemic toxicity.
Keywords: Glioblastoma; astrocytoma; radioimmunotherapy; BC-4 antibodies